Compounds of neutralization (Mg²+ Y Ca²+)associated with the atmopheric deposition (wet-only and dry only) - Chaves-Romero, Aura Leticia (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2008)
Ths estudy was realized in a rural zone (Andorra Teruel) the NE of Spain, where I determine the contributing (marine/continental) relation of the compounds of neutralization (Mg²+  Y   Ca²+), that accompany the atmospheric deposition dry and humid in separated form. The analysis of the results revealed a similarity of the ratio Mg²+ / Ca²+  between  the wet and dry events; different case happened with the relation Mg²+/ Cl- where the wet deposition showed major extraction of chlorides (20%) that the athmospheric dry deposition, owed possibly to the solubility of his you sales.  It is necessary to highlight that in our case, the nitric acid was neutralized by the NH3  in the wet deposition, and in provide lightly top for calcic carbonate proceeding from the particles terrígenas. These cconclusions arew similar to the obtained ones for Pakkanen, (1996) and Harrison and Kito (1990). Also it observe the Ca² as the major agent of neutralization of the nitric acid  (dry depositon) and that interaction Na+ - HNO3 is not probale in the wet deposition.